The use of supplementary materials in EFL classes: a comparative analysis of public and private high schools - Mejía Torres, Cosme Freddy (2014)
The study The use of supplementary materials in EFL classes: a comparative analysis of public and private high schools is focused on a comparative analysis in public and private high schools which was done in order to identify the type of supporting materials used in high school, and to see how these materials were applied in the English teaching-learning process. The research was carried out in 1st, 2nd, and 3rd years of senior high school at the Eloy Alfaro public high school in Cariamanga and with the students from the Lauro Guerrero private high school in Loja. The quantitative and qualitative methods were used to validate the use of supplementary materials, as well as to establish variables and indicators. In the public high school, few supplementary materials were used; while in the private high school, the use of these materials increased. The materials were pertinent both to the topic and the objectives of the lesson. In addition, the supplementary material used during the lessons was appropriate to the age and knowledge of the students. Students were also motivated.